Reinforcing Transparency: The Synergistic Role of Forensic Accounting and Investigative Auditing in Combating Corporate Fraud - Mujahidin, A. Fajar (Journal of Principles Management and Business, 2025)
This study aims to analyze the role of forensic accounting and investigative auditing in preventing and detecting corporate fraud through a synthesis of recent empirical and theoretical findings. Using a qualitative narrative literature review approach, the research examines 20 peer-reviewed studies published between 2020 and 2024 that discuss the integration of forensic audit practices, internal control mechanisms, and good corporate governance. Data were analyzed through thematic synthesis and critical comparison to identify recurring patterns, methodological differences, and research gaps. The findings reveal that forensic accounting and investigative auditing contribute significantly to fraud prevention and detection when supported by competent auditors, robust governance frameworks, and adequate institutional and technological resources. Conversely, their effectiveness diminishes in organizations lacking coordination, regulatory clarity, or adequate training in forensic techniques. The study also highlights that digitalization, whistleblower protection, and data analytics serve as important enhancers of forensic audit effectiveness. The implications emphasize the need for organizations to strengthen governance systems, invest in auditor competence, and standardize forensic audit frameworks to ensure sustainability and transparency in financial management. The novelty of this research lies in its integrative synthesis, which bridges theoretical frameworks and empirical findings to construct a comprehensive model explaining how forensic accounting and investigative auditing jointly reinforce corporate fraud prevention and detection.